Deploying and evaluating multiattribute product recommendation in e-markets. (14th January 2008) - Manouselis, Nikos
Evaluation of proposed recommender systems before their final deployment, under experimental conditions close to the actual e-market ones, can prove of significant added value for system developers. The objective of this paper is to present the results of a pilot evaluation experiment for a product recommendation system of an electronic market (e-market). More specifically, it first presents the design of a product recommendation algorithm that is based on MultiAttribute Utility Theory (MAUT). Then it describes its implementation and evaluation for supporting consumers' wine selection in agricultural e-markets. This takes place through a small-scale experiment that engages a variety of evaluation measures and which involves both simulated data, as well as, data from a focus group of real wine consumers. This pilot evaluation may serve as a useful case study for e-market operators and developers who wish to evaluate multiattribute product recommendation systems before they deploy them online.